Apakah Ada Peluang Ketika Krisis? Pandemi Covid-19 dan Kinerja Perusahaan di Bursa Efek Indonesia - Ramel Yanuarta RE; Alfitriani Alfitriani; Silvia Netsyah (Jurnal Ecogen, 2023)
The purpose of this study was to determine the impact of Covid-19 on company performance on the Indonesian stock exchange, particularly the consumer cyclicals and consumer non-cyclicals sectors in 2017-2021. The sample of this study is the consumer cyclicals and consumer non-cyclicals sectors with 120 issuer and selected using with purposive sampling technique. The analytical method used is panel data regression analysis using Stata. The results show that (1) Covid-19 pandemic has a negative impact on the performance in the consumer cyclicals than on non-cyclicals consumer sectors, (2) when the firm’s investment scale is smaller, the negative impact of COVID-19 pandemic on firm performance is not more pronounced, (3) the negative impact of COVID-19 pandemic on firm performance is not more pronounced, if a firm’s sales revenue is less.